Spray Dried Extract of Phormidium valderianum as a Promising Source of Natural Antioxidant - Dipan Chatterjee; Paramita Bhattacharjee; Gour Gopal Satpati; Ruma Pal (International Journal of Food Science)
Microencapsulation of antioxidant-rich fraction obtained by supercritical carbon dioxide extraction (at 50°C, 500 bar with extraction time of 90 min, and flow rate of CO2 at 2 L/min) of lyophilized biomass of Phormidium valderianum was carried out in a spray dryer using maltodextrin and gum arabic. Microencapsulation conditions that provided the best combination of phytochemical properties such as antioxidant activity, phenolic content, and reducing power with reasonable powder yield were an inlet temperature of 130°C and wall material composition as maltodextrin: gum arabic = 70 : 30. Toxicological study reported that the Anatoxin-a content of this encapsulated powder was below the limit of detection of HPLC. Storage study established that encapsulation of this antioxidant-rich algal extract resulted in eight times enhancement of half-life (T1/2) values. The release profile of microencapsulated antioxidant-rich fraction from the encapsulated powder was found to follow first order anomalous transport kinetics. Therefore, this microencapsulated algal extract with minimum toxicity is a source of natural antioxidant and could have promising use as novel dietary supplement.